Exploring Islamic Local Wisdom of Halal Tourism Destinations toward Return Visits ‎and the Perception of Islamic Socio-Cultural Responsibility - Alam, Azhar; Karima, Nida Izzatul; Talib, Mohamed Syazwan Ab; Sawari, Siti Salwa Md (Dirasat: Human and Social Sciences, 2025)
Objectives: The purpose of this study is to analyze how Islamic local wisdom and socio-cultural responsibility influence Muslim tourists’ decisions to revisit halal destinations. Methods: The research employs a qualitative phenomenological approach, collecting data through interviews and observations with 16 respondents from various halal tourism sites in Indonesia. Results: The results reveal that Islamic local wisdom, such as unique cultural landmarks, Qur’anic teachings in natural settings, and Islamic architectural elements, significantly enhance tourists’ intentions to revisit. Additionally, the integration of Islamic values into cultural offerings and local cuisine contributes to a positive tourist experience. The study also highlights the importance of social and cultural responsibility, including adherence to Islamic ethical principles in tourism management, providing halal facilities, and empowering the community. The originality of this research lies in its comprehensive examination of the dual impact of local wisdom and social and cultural responsibility on halal tourism, offering new insights into practical strategies for attracting and retaining Muslim tourists. Conclusions: This study explores the impact of Islamic local wisdom on halal tourism destinations in Indonesia, focusing on the reconsideration of Islamic social and cultural responsibility perceptions. The study contributes to the literature by emphasizing the role of Islamic values in enhancing tourist satisfaction and promoting sustainable tourism practices. The study recommends the continuous integration of Islamic local wisdom into tourism offerings, the enhancement of halal facilities, and the promotion of ethical tourism practices. Future research should explore the long-term effects of these strategies on tourist behavior and destination sustainability.